THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN ASSISTED REPRODUCTIVE TECHNOLOGY (ART): EXAMINING THE LEGAL AND ETHICAL IMPLICATIONS. - Oyetola Mary Adeniyi,; Vera B. Monehin, (ABUAD Law Journal, 2024)
In a world where Artificial Intelligence (AI) is rapidly gaining prominence, its potential application in the field of Assisted Reproductive Technology (ART) cannot be overlooked. AI in ART has revolutionized the field of reproductive medicine, promising enhanced efficiency and outcomes. This article delves into the legal and ethical considerations surrounding this burgeoning intersection. AI algorithms are increasingly utilized in ART procedures such as in vitro fertilization (IVF), embryo selection, and gamete screening, optimizing success rates, and minimizing risks. AI holds promise. This study explores the intersection of AI and ART, investigating the legal challenges arising from their integration. It scrutinizes the implications of employing AI in reproductive technologies, delving into concerns such as data privacy, consent, liability, and the potential necessity for novel regulatory frameworks. The research provides a comprehensive overview of the evolving legal and ethical landscape in this domain. Employing a doctrinal methodology, which involves analyzing legal principles and doctrines, the study aims to contribute to the ongoing discourse on the ethical and legal framework essential for ensuring the responsible and equitable utilization of AI in ART. Despite the numerous challenges, the amalgamation of AI and ART is poised to significantly influence the trajectory of medical advancement in the future.